2015
DOI: 10.1007/s12639-014-0639-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage temperature on survival and infectivity of three indigenous entomopathogenic nematodes strains (Steinernematidae and Heterorhabditidae) from Meghalaya, India

Abstract: Three locally isolated strains of entomopathogenic nematodes (EPNs), viz. Heterorhabditis indica, Steinernema thermophilum and Steinernema glaseri, from Meghalaya, India were characterized in terms of storage temperature and survival and infectivity of their infective juveniles (IJs). The survival and infectivity of nematode IJs was studied at, 5 ± 2 and 25 ± 2°C, for a period of 120 days, using deionized water as storage medium. The viability of nematode IJs was checked by mobility criterion at different stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 14 publications
1
9
2
Order By: Relevance
“…Investigating the impact of single and combined climate related drivers onto EPN survival and efficacy revealed no interaction between elevated temperature, CO 2, and decreased precipitation. While temperature is known to be a major driver of EPN survival and infectivity (Pervez et al 2015;Lalramliana & Yadav 2016;Aatif et al 2020), we did not find any impact of warming in our study. This discrepancy may be explained by the low range of temperature used in our study (19.6 -23°C) compared to the described beneficial temperature range (25 -30 °C) (Pervez et al 2015).…”
Section: Discussioncontrasting
confidence: 90%
“…Investigating the impact of single and combined climate related drivers onto EPN survival and efficacy revealed no interaction between elevated temperature, CO 2, and decreased precipitation. While temperature is known to be a major driver of EPN survival and infectivity (Pervez et al 2015;Lalramliana & Yadav 2016;Aatif et al 2020), we did not find any impact of warming in our study. This discrepancy may be explained by the low range of temperature used in our study (19.6 -23°C) compared to the described beneficial temperature range (25 -30 °C) (Pervez et al 2015).…”
Section: Discussioncontrasting
confidence: 90%
“…The negative effect of age on virulence is supported by a study by Lalramliana et al [ 56 ], who reported that the highest virulence of S. thermophilum and S. glaseri toward G. mellonella was observed in the first month of storage at 25 °C. After 3 and 4 months of storage, virulence began to significantly decrease, in both S. thermophilum and S. glaseri , respectively.…”
Section: Discussionmentioning
confidence: 72%
“…An explanation for the differences in virulence observed in the above-mentioned studies remains unknown. However, the virulence and insect killing effectivity of EPNs can be affected by many others factors, e.g., temperature [ 52 , 56 , 58 , 59 ], UV radiation [ 60 ], and others. Therefore, it is necessary to always specify IJs age and storage parameters in the experimental design.…”
Section: Discussionmentioning
confidence: 99%
“…In agricultural use, it is not uncommon for EPNs to endure extended storage times. It has been previously demonstrated that storage temperature may affect both the survival and infectivity of EPNs [ 23 , 24 ]. Since previous work had demonstrated that the response of some EPNs to prenol were affected by moderate storage times [ 5 , 18 ], we wondered how longer time periods of storage/aging would impact the IJs’ behavior.…”
Section: Resultsmentioning
confidence: 99%